Analysis and comparison of tear protein profiles in dogs using different tear collection methods - Ritchoo S. (2023)
Background: Tear proteomic analysis has become an important tool in medical and veterinary research. The tear collection method could influence the tear protein profile. This study aims to evaluate the protein profiles of dog tears collected using microcapillary tubes (MT), Schirmer tear strips (ST), and ophthalmic sponges (OS). Methods: The tear samples were collected using MT, ST, and OS. Tear protein profiles were analyzed using two-dimensional electrophoresis (2-DE) and the different protein spots’ expression was compared. Fourteen protein spots were identified using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: Tear protein concentrations ranged from 2.80 to 4.03 μg/μL, with no statistically significant differences among collection methods. Protein expression in each collection method differed in terms of both the number and intensity of the spots. There were 249, 327, and 330 protein spots found from tears collected with MT, ST, and OS, respectively. The proteins albumin, haptoglobin, and lactoferrin identified from OS were found to have higher spot intensities than other methods of collection. The use of MT demonstrated the downregulation of nine proteins. Conclusions: The recent study supported that tear protein analysis is affected by different tear collection methods. Although ST is commonly used for tear collection, it provides insufficient information to study particular tear proteins.